SCREENING HIGH RESOLUTION COMPUTED TOMOGRAPHY (HRCT) CHEST AMONG PATIENTS UNDERGOING CARDIAC INTERVENTIONS DURING COVID-19 PANDEMIC; RADIOLOGICAL FINDINGS AND CLINICAL ASSOCIATIONS - Waheed, Sidra; Tuyyab, Farhan; Raja, Waseem; Saif, Mohsin; Nayyar, Bushra; Bokhari, Syed Aown Raza Shah (Pakistan Armed Forces Medical Journal, 2020)
Objective: To study the HRCT chest findings in patients undergoing cardiac interventions during COVID-19 era. Study Design: Cross sectional analytical study. Place and Duration of Study: Armed Forces Institute of Cardiology & National Institute of Heart Disease (AFIC/NIHD) Rawalpindi, from Apr 2020 to May 2020. Methodology: All the admitted cardiac patients who were to undergo any invasive cardiac intervention underwent plain HRCT chest and polymerase chain Reaction (PCR) for SARS-CoV-2 simultaneously. One hundred and ten patients were studied. We analyzed preexisting respiratory illnesses, clinical, echocardiographic and radiological features. Data recording, storage, assessment and analysis was done by using SPSS-21. Results: Our study included 110 patients (87 Male, 23 Female, median age 52 Years). Common reasons for admission were coronary angiography 43 (39.1%), acute Left Ventricular Failure (LVF) 30 (27.3%), Percutaneous Coronary Intervention (PCI) 13 (11.8%) and chest pain evaluation 10 (9.1%). Cardiomegaly (29.1%) followed by consolidation (9.1%) were commonest radiological finding. Two third patients had abnormal HRCT chest but only few had radiological findings either suspicious (6.4%) or indeterminate (11.8%) for COVID-19. Respiratoy symptoms, positive PCR for COVID-19 and severe Left ventricular dysfunctions were correlated with abnormal HRCT findings, correlation being statistically significant (p-value <0.05). Conclusion: HRCT chest is a non-invasive and highly sensitive imaging modality, which can rapidly help in identifying, and isolating suspected cases of novel corona virus as well as in diagnosing unknown pre-existing lung diseases in cardiac patients.